PERSEPSI WISATAWAN MANCANEGARA TERHADAP FASILITAS DAN PELAYAAN DI CANDI PRAMBANAN - Kartika F. Nieamah (Pusat Studi Pariwisata Universitas Gadjah Mada, 2014)
Candi Prambanan is the largest Hindu temple complex in Yogyakarta and became an icon of tourism, has been recognized by UNESCO as a cultural site. The study aims to analyze and describe the perception of foreign tourists before the visit to the quality of amenities and services at Prambanan. The method used is qualitative by linking the three variables, namely the perception before the visit, expectations and perceptions of the quality of an object. Data collection techniques using interviews. The process of data analysis data collection (interviews, observation, documents) and performed data reduction, encoding in accordance with the parameters and indicators and interpretation. The validity of the test is done by using triangulation. The results showed that the perception of tourists before been stated that the Prambanan temple is beautiful, has a unique architecture, and has an interesting history. The motivation is the need curiosity. The expectation is hoping to see the splendor of the temple, can learn the difference Hindu and Buddhist architecture, hoping temple which will be seen to be greater than imagined, and can see a large temple complex. While the perception after the visit is to have a very high historical value, has an interesting legend, the temple complex of Prambanan temple has great though many temples were missing but did not detract from the beauty, has a very unique architecture and interesting, Prambanan temple complex is well organized. Prambanan Temple is also safe, comfortable, clean, and beautiful as a city park. Thus, comparison of perceptions and expectations of tourists before and after berkunjunga is appropriate or even exceed expectations.